A nonlinear grain-based fatigue damage model for civil infrastructure under variable amplitude loads. (November 2017) - Yuan, Hao; Zhang, Wei; Kim, Jeongho; Liu, Yongming
Abstract: To assess fatigue damage accumulation for civil infrastructure, Miner's rule or linear elastic fracture mechanics (LEFM) are usually used in many codes and specifications. However, large uncertainties are found when the short cracks are initiated. Currently, most physics-based models for crack initiation are built for constant amplitude loads (CA). Since the environmental or service load-induced stresses at local details for crack initiation are time-variant, these physics-based models could not be directly applied for real civil infrastructure. In this paper, a two-fold nonlinear grain-based fatigue damage model is proposed to process the variable amplitude loads (VA) induced fatigue damages by combining Persistent Slip Band (PSB)-based short fatigue crack model and grain-based Miner's rule. In the sub-grain regime, linear damage accumulation is adopted. For the repeated stress blocks with variable amplitude, the stress block is rain-flow counted and the damage accumulation is modeled as short crack extension. Therefore, the crack associated damage will be accumulated grain by grain until it reaches characteristic length of a long crack. The damage accumulation from a stress block is added for each grain. Effect from subcritical loads is also considered in this damage accumulative model. Finally, a numerical demonstration is performed on statistical representative elements under variable stress histories from a long span bridge.